DETERMINATION OF BACKPACK MASS LIMIT FOR STUDENTS IN A UNIVERSITY IN ABEOKUTA, SOUTHWESTERN NIGERIA - SALAMI OLASUNKANMI ISMAILA (Journal of Engineering Studies and Research)
The aim of this study was to use the Froude number to determine the mass of the backpack that a student should carry in tertiary institutions. A model was developed using the Froude number with leg length and power of the students as inputs. It was established that a student in tertiary institutions should carry a backpack with a mass of at most 10 % of the body mass. Similar studies are recommended for primary and secondary schools.